Abandoned Public Housing Projects Reactivation: A Sustainable Approach - Kwadwo Twumasi-Ampofo; Ernest Osei –Tutu; Isaac Decardi-Nelson; Prince Abrokwa Ofori (Innovations in Science and Technology Vol. 3, 2022)
There is the urgent to provide housing to reduce the ever increasing housing deficit in Ghana. The root causes include improper planning and incoherent political activities, mismanagement and consequent abandonment of public housing projects are not far-fetched. Even projects established in the colonial period to provide shelter have been abandoned. Some housing projects initiated for mere selfish politics (face-saving purpose) only to be abandoned along the way. Worse still, others were commenced to please electorates so as to avert threats and disloyalty from them, while politicians are somewhat aware that the government’s finances cannot complete those projects. This study has the objective of developing a sustainable approach to reactivate abandoned public housing projects. The study brings out three major categories of causes for public housing project abandonment, namely; poor project implementation, negative politics practiced by the governments that culminate in abandonment of public projects and lack of proper structures to ensure the continuation of public projects when there is a change in government. These three major categories of causes are iteratively refined and eventually, the root causes emerged. This information is then used as a guide, with the aid of “Cause and Effect Diagram”, to generate a model that could be used to revive abandoned housing projects as well as ensure its sustenance. The model presented three main factors that when adopted could lead to project reactivation. These include: proper implementation of public housing project, positive politics practice by government and adequate structures that ensure continuation of public housing projects when there is a change in government.